Business Feasibility Study and Added Value of Broccoli Stem Stick Products at CV Tani Organik Merapi - Yolanda Desi Anggraini; Dahri Tanjung (Agribusiness Journal, 2025)
CV Tani Organik Merapi is a company that produces organic vegetables, one of which is broccoli. The discarded broccoli trimmings are a weakness of the company. The solution that can be done by the company is to process the trimmings into broccoli stem sticks. This study aims to determine consumer preferences, analyse and compile business feasibility and add value to the O'Bro Stik business. The methods used include conjoint analysis, business feasibility of non-financial and financial aspects, and added value. The results of consumer preferences indicate that the attributes that consumers consider before purchasing O'Bro Stik are texture, price, and packaging. The results of the non-financial and financial analysis are declared feasible with an NPV of Rp86,166,474; IRR 102.17%; gross B/C 4.58; net B/C 1.40; and a payback period of 2.0 years. The switching value results show that the maximum tolerance limit for changes in production is 30.13% and 534.65% for increases in wheat flour. The value-added analysis produces a significant value of 47.70%.